First Evidence of Increased Plasma Serotonin Levels in Tako-Tsubo Cardiomyopathy. (23rd September 2013) - Rouzaud Laborde, C.; Delmas, C.; Mialet-Perez, J.; Pizzinat, N.; Biendel-Picquet, C.; Boudou, N.; Dumonteil, N.; Spreux-Varoquaux, O.; Carrié, D.; Galinier, M.; Parini, A.; Lairez, O.
Abstract : Background . There is no data about the serotonergic activity during the acute phase of Tako-Tsubo Cardiomyopathy (TTC). The objective of our study was to investigate evidence of serotonin release from patients with TTC in comparison with patients with ST elevation myocardial infarction (STEMI) and healthy control subjects (HCS). Methods and Results . Plasma serotonin levels in 14 consecutive patients with TTC were compared with those in 14 patients with STEMI and 14 HCS. Plasma serotonin levels at admission were markedly higher in patients with TTC and STEMI as compared to HCS (3.9 ± 4.6, P = 0.02 versus control; 5.7 ± 5.6, P = 0.001 versus control; and 1 ± 0.4  ng/mL, resp.). There was no difference in serotonin levels between patients with TTC and those with STEMI (P = 0.33 ). Conclusion . This finding suggests that serotonin could participate to the pathophysiology of TTC.